Capital flows and macroprudential policies - A multilateral assessment of effectiveness and externalities - John Beirne; Christian Friedrich (European Central Bank (ECB), 2014)
This paper assesses the effectiveness and associated externalities that arise when macro- prudential policies (MPPs) are used to manage international capital flows. Using a sample of up to 139 countries, we examine the impact of eight different MPP measures on cross-border bank flows over the period 1999-2009. Our panel analysis takes into account the structure of the banking system as well as the presence of potential cross-country and cross-asset class spillover effects. Our results indicate that the structure of the domestic banking system matters for the effectiveness of MPPs. We specifically find that a high share of non-resident bank loans in the MPP-implementing country reduces the domestic effectiveness of most MPPs, while a high return on assets in the domestic banking system has the opposite effect. Our results on the spillover analysis indicate that both types of spillover can occur. First, we find that a high return on assets in the banking system of countries other than the MPP-implementing one leads to a reduction, and a greater degree of trade integration leads to an increase in spillovers across countries. However, the economic significance of the results suggests that only a limited number of countries will tend to experience substantial geographical spillover effects. Second, we also find some evidence of spillover effects across asset classes within countries.
Keywords: F3; F5; G01; G11; 330; banking system; international capital flows; macroprudential policies